Pengaruh Kompetensi, Komunikasi Internal dan Gaya Kepemimpinan terhadap Kinerja Karyawan Pada PTPN IV Unit Gunung Bayu Kabupaten Simalungun - Fahri Fahri; Normansyah Normansyah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee performance at PTPN IV Gunung Bayu has not yet reached the expected production targets, indicating the presence of internal organizational factors that need to be addressed. This study aims to examine the effect of competence, internal communication, and leadership style on employee performance, both partially and simultaneously. The research employs a quantitative explanatory approach using primary data collected through questionnaires distributed to 60 employees selected from a population of 150 using the Slovin formula. Data were analyzed using multiple linear regression supported by SPSS. The results show that competence, internal communication, and leadership style each have a positive and significant effect on employee performance. Simultaneously, the three variables also significantly influence performance. The coefficient of determination indicates that 42.9% of employee performance can be explained by these variables, while the remaining proportion is influenced by other factors outside the model. These findings highlight the importance of strengthening employee competence, improving internal communication, and applying appropriate leadership practices to enhance organizational performance.